Nan Ka Sanang Realitas dari Peristiwa Tolak Bala dalam Tradisi Basapa di Taeh Bukik di Kabupaten Lima Puluh Kota - Putri, Sonya Prima; Emri, Emri; Wahyuni, Wahida; Oktavianus, Oktavianus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Nan Ka Sanang dance is inspired by the Basapa tradition in Taeh Bukik, Lima Puluh Kota Regency, a tradition of praying during the month of Syafar as a way to ward off disaster and seek inner peace. This work depicts the reality of the tolak bala event in the basapa tradition, namely the spiritual journey of humans who come bringing disaster, anxiety, and hope, toward a point of purity through prayer and drawing closer to God. This work is danced by eight dancers accompanied by techno music. The methods used in creating this dance work are exploration, improvisation, and formation. The movements are developments of movements found in the basapa activity, namely sitting, walking, standing, and praying. This work uses a tray as a prop, symbolizing togetherness towards a common goal. This work is created with a religious theme and a pure style, consisting of three lines. It was performed at the Huriah Adam Performance Hall, Indonesian Institute of the Arts, Padangpanjang.